Покращення збуту сільськогосподарської продукції рослинництва - Павлова, Галина Євгеніївна; Pavlova, Halyna; Киричок, В. О.; Kyrychok, V. (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2024)
В даній роботі дослідженно можливості покращення збуту сільськогосподарської продукції рослинництва. Основна мета дослідження полягає в ідентифікації проблем та визначенні оптимальних стратегій для збільшення обсягу продажу сільськогосподарської продукції. У роботі проаналізовано основні фактори, що впливають на збут рослинницької продукції, такі як забезпеченість ринку, конкуренція, технології та інновації. В результаті дослідження було виявлено, що для покращення збуту необхідно враховувати ці фактори. Додатково, у роботі розглянуто та проаналізовано основні методи та інструменти маркетингу для підвищення збуту. Серед них маркетингові дослідження, реклама, розробка нових каналів та залучення управлінських інструментів. Отже, визначено, що дана робота надає цінні рекомендації для підвищення збуту сільськогосподарської продукції рослинництва та розвитку цієї галузі. Застосування виявлених маркетингових методів та розробка стратегій можуть допомогти фермерам та сільськогосподарським підприємствам ефективно підвищити свої продажі й отримати стабільні прибутки. This work examines the possibilities of improving the sale of agricultural products of crop production. The main purpose of the study is to identify problems and determine optimal strategies for increasing the volume of sales of agricultural products. The paper analyzes the main factors affecting the sale of plant products, such as market availability, competition, technologies and innovations. The main crops grown by agricultural enterprises, which accounted for the largest sown areas were cereals and legumes (mostly wheat and corn), among industrial crops –sunflower and soybeans. The instability of agricultural enterprises in Ukraine in recent years is due to the lack of proper understanding of the functions of the state in relation to macroeconomic regulation of economic efficiency, as an important element of the mechanism of crop production in the context of innovative development of Ukraine.As a result of the study, it was found that these factors must be taken into account in order to improve sales. In addition, the main marketing methods and tools for increasing sales are considered and analyzed in the work. Among them are marketing research, advertising, development of new sales channels and involvement of management tools.The production of agricultural products in Ukraine has taken a leading place in the structure of the Ukrainian economy for more than a dozen years, but in connection with the unstable economic situation in the country in recent years and the beginning of a full-scale invasion, the market for the sale of plant products in Ukraine has been significantly shaken. continuous sales, both agricultural producers and the population were not found. However, the need to improve the sales process is constantly growing, so scientists have come up with a number of innovations that, in turn, would satisfy the interests of both consumers and sellers of these products. The analysis of the received data showed that the effective use of these methods and tools can have a positive effect on the sale of agricultural products of crop production. In addition, it is important to develop strategies to expand the range of products and improve quality, which can also contribute to increasing product sales. So, it is determined that this work provides valuable recommendations for increasing the sale of agricultural products of crop production and the development of this industry. Applying identified marketing methods and developing strategies can help farmers and agricultural enterprises effectively increase their sales and obtain stable profits.
Improvement of the sale of agricultural and plant production
Keywords: збут; sales; експорт; export; сільськогосподарська продукція рослинництва; agricultural products of crop production; сільськогосподарське підприємство; agricultural enterprise; маркетинг; marketing; підприємство; enterprise; удосконалення; improvement; рослинництво; crop production